HUKUM ISLAM DAN MULTIKULTURALIS- PLURALITAS DI INDONESIA - Hannani, Hannani (DIKTUM: Jurnal Syariah dan Hukum, 2013)
Culture is a whole system of ideas, actions and products of human endeavor to fulfill their lives by learning, all of which are arrayed in people's lives. Pluralism is understood that a plurality of saw it as a reality that is positive and as a necessity for salvation of mankind. Multiculturalism is a recognition that some of the different cultures can exist in the same environment and benefit from each other. Or the recognition and promotion of cultural pluralism. Since the early development of Islam as a conception of reality has accepted socio-cultural accommodation. This accommodation is increasingly seen as an Islamic region evolved such that it became a worldwide religion. In certain cases, accommodation is created in such a way, giving rise to "a variant of Islam". Pluralistic society (plural) where people from various ethnic backgrounds, tribes, nations and religions come together and live together will pose its own challenges that need to be answered by the urban community by developing properties that match the circumstances. The properties that match the state of society is this city is a multicultural civil society - and of course involve certain attitudes are becoming multicultural society demands. These gestures include, among others, inclusivism, humanism/egalitarianism, tolerance, and democracy.